Peta Politik di Sulawesi Selatan pada Awal Islamisasi - Syamsuez Salihima (Rihlah : Jurnal Sejarah dan Kebudayaan, 2015)
This study aims to reveal the political map in South Sulawesi at the beginning of Islamization. There are three sub-problems that were subjected to this study, namely: (1) How did the social cultural situation of South Sulawesi society? (2) How did the political map both before and after Islam was accepted as the official religion in South Sulawesi Kingdom? (3) How did the impact of Western colonizers on the political landscape in South Sulawesi?In order to uncover the answers of those problems, researcher applied the historical method. The sources will be used is library literature. Library literature includes conceptions literature and research data. The data were obtained wiil be analyzed using qualitative data analysis.As a result of this research: First, the social cultural situation of South Sulawesi community can be seen by three tribes in the South Sulawesi, namely Bugis, Makassar and Toraja. These three tribes, had a different socio-cultural background, however, there are a same things in those tribes. Secondly, before the arrival of Islam in South Sulawesi, there are several kingdoms. That kingdoms had formed an alliance and still continue during the coming of Islam. Although the backgrounds and different forms of partnership. Third, the arrival of the West, particularly VOC brought penetration in various aspects of community life in South Sulawesi. Especially the political aspects, the Netherlands created hegemony, among the political forces. In that political forces appeared a lot of  conflict, especially among the Gowa Kongdom with Bone Kingdom.